Influence of Transformational and Transactional Leadership Style toward Food Safety Management System ISO 22000:2018 Performance of Food Industry in Pati Central Java - Agus Purwanto; Masduki Asbari; Priyono budi Santoso (Politeknik Negeri Bengkalis, 2019)
The purpose of this study is to analyze the influence of transformational and transactional leadership styles to the performance of the implementation of a food safety management system ISO 22000: 2018 at PT. SPN a food packaging beverage industry located in Pati Central Java. The study population are employees at PT. SPN as many as 88 people and data collection methods by giving a census questionnaire to all employees. The analysis tool this study uses SEM (Structural Equation Model) the LISREL program version 8.70. The results show that the transformational leadership style have positive and significant affected to the performance of implementation ISO 22000: 2018 and the transactional leadership style also have significant and positive affected the performance of implementation of the food safety management system ISO 22000:2018.